2022
DOI: 10.15170/mm.2021.56.01.03
|View full text |Cite
|
Sign up to set email alerts
|

A game of perceived risk in social commerce transactions – A suggestion for the integration of the trust (payment) feature on social commerce platform sales

Abstract: THE AIMS OF THE PAPER To decrease perceived risks and opportunism in social commerce transactions, many social media sites have integrated the checkout feature to their model of social media platform sales, which allows customers to immediately check out without being navigated to other websites. However, this feature is not agreeable to many merchants due to the uncontrollable customer data and other problems. Therefore, the purpose of the paper is to discuss whether merchants should set up the checkout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies also revealed the significant impact of perceived risk in the prepurchase stage. Accordingly, perceived risk lowers consumers' purchase intention in e-commerce (He et al 2022, Sharma et al 2022, PhamThi 2022. According to Lim et al (2019), perceived risk negatively relates to buying intention in online shopping.…”
Section: Marketing and Menedzsmentmentioning
confidence: 99%
“…Previous studies also revealed the significant impact of perceived risk in the prepurchase stage. Accordingly, perceived risk lowers consumers' purchase intention in e-commerce (He et al 2022, Sharma et al 2022, PhamThi 2022. According to Lim et al (2019), perceived risk negatively relates to buying intention in online shopping.…”
Section: Marketing and Menedzsmentmentioning
confidence: 99%
“…However, the e-commerce environment is characterized by the information asymmetry in terms of product and service qualities existing between the buyers and sellers (Shao et al, 2021), between different online sellers, and between the sellers and the platform managers (Nana et al, 2022). Consequently, game theory may contribute to explaining the opportunistic behaviours existing in online transactions (PhamThi, 2022).…”
Section: Theorymentioning
confidence: 99%